Farmer’s Field Evaluation of Direct Seeded Rice vis-à-vis Puddled Transplanted Rice in Kapurthala, Punjab - Bhatt, Rajan; Singh, Pritpal (Indian Journal of Extension Education, 2022)
The direct seeded rice (DSR) has emerged as an economically viable and sustainable option for timely rice establishment due to labor shortage amid Covid-19 pandemics. The crop production practices differ greatly among puddled transplanted rice (PTR) and DSR. Therefore, we compared the performance of different rice varieties viz. PR-121, PR-126 and Pusa-44 under two contrasting establishment methods (PTR vs. DSR). The study highlights that of the total area under rice, the highest area under DSR was in Sultanpur Lodhi block (about 68.2%), while the lowest area in Dhilwan block (about 41.9%). Results revealed higher benefit-cost ratio of rice establishment under DSR technology, compared with the PTR technology, regardless of the rice variety due to reduced (about 23.9%) cost of cultivation associated with rice establishment under DSR technology. About 68.9 per cent of the respondents perceived PTR as low cost effective, while about 4.7 per cent perceived PTR as highly cost effective. Conversely, about 16.0 per cent of respondents perceived DSR as low cost effective, while a large proportion (about 55.7%) perceived DSR as highly cost effective. About 14.1, 76.4 and 10.4 per cent of PTR farmers, while about 10.4, 69.8 and 14.1 per cent of DSR farmers perceived it as low, medium and highly profitable.
Keywords: Direct seeded rice; Puddled transplanted rice; Economic analysis; Yield difference; Establishment methods; Farmer’s perception